The Effect of the Multimodal Learning Model Using Animation Video on Islamic Elementary School Students’ Learning Outcomes - Gea, Sarifah Hanum; Setiawati, Dewi Teti; Ridwan, M. Bagus; Sukriyah, Elvi; Mardianto, Mardianto; Haidir, Haidir (Jurnal Basicedu, 2023)
This research is motivated by the lack of development of educators in teaching in the digital era which has an impact on the learning outcomes of elementary school students, especially PAI lessons. In line with this, the research aims to describe learning outcomes in multimodal models using animated videos and prove the effectiveness of learning on PAI learning outcomes. This research was carried out using two types of quantitative research, namely descriptive research and experimental research. This research was carried out in two classes that had different characteristics, both in terms of students' backgrounds and students' general academic abilities. Data was collected through observation sheets and tests. Data is processed using statistical regression tests (regression). Based on the results of the study, it was concluded that the multimodal learning model using video animation had an effect on the learning outcomes of PAI with the acquisition of a Significance Value of 0.001 <0.05. Based on this, the multimodal learning model using video animation can be used as an alternative to improve Islamic education learning outcomes that have a variety of backgrounds in learning styles (kinesthetic, audio and visual).